2020
DOI: 10.3390/pr8060718
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Enhanced Liquefaction of Pulp from Mango (Mangifera indica L.) cv. Totapuri Using Ultrasound-Assisted Enzyme Pretreatment

Abstract: The effect of ultrasound and enzyme pretreatment (with pectinase, amylase, and cellulase) on the physicochemical properties (yield, viscosity, total soluble solids, and total phenolics) of mango juice was evaluated through a set of six experiments. Ultrasonication treatment alone showed no influence on juice yield (54.6 ± 1.1%). However, the combined uses of ultrasonication with a pectinase or the enzyme mixture significantly increased the yield (94.1 ± 1.4% and 80.0 ± 2.1%, respectively) and decreased the enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
(29 reference statements)
2
4
0
Order By: Relevance
“…It was observed that the yield of noni juice extracted by the combined ultrasound and enzymatic method was higher than that of juice sample treated by the individual method. Similar results were observed for the extraction of acerola mash [15] and mango juice [16] . In addition, the sequence of enzyme-assisted ultrasonication significantly ( p < 0.05) effected the juice yield.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…It was observed that the yield of noni juice extracted by the combined ultrasound and enzymatic method was higher than that of juice sample treated by the individual method. Similar results were observed for the extraction of acerola mash [15] and mango juice [16] . In addition, the sequence of enzyme-assisted ultrasonication significantly ( p < 0.05) effected the juice yield.…”
Section: Resultssupporting
confidence: 86%
“…Dang et al [15] boosted the juice yield and nutritional quality of acerola mash through employing a pectinase-assisted ultrasonication method. Furthermore, it was found that pectinase-assisted ultrasonication exerted a significant effect on the yield-promotion and viscosity-reduction of mango juice [16] . In addition, the applications of combined ultrasound and enzymatic treatment on banana [17] , plum juice [18] and dragon juice [19] were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies on the application of such an integrated method for juice pretreatment are limited. Despite its few demonstrations for the fruit pulp liquefaction of grape (Lieu & Le, 2010), banana (Bora et al, 2017), Sohiong (Vivek et al, 2019), plum (Olawuyi et al, 2020), and mango (Reddy et al, 2020), no study has yet been performed for dragon fruit juice.…”
Section: The Combination Of Enzymatic Maceration and Ultrasonicationmentioning
confidence: 99%
“…TPC values did not change much with sonication, but a decrease in raw myrtle juice was observed with enzyme application. Studies in which TPC increased after sonication and (Bhat & Goh 2017;Kidon & Narasimhan, 2022 ) enzyme application (Wang et al, 2009, Reddy et al, 2020, Radziejewska-Kubzdela et al, 2020 have been reported in the literature. In our study, when the FRAP value was compared with the control group, it did not change much at the end of sonication, but FRAP values decreased after enzyme treatment.…”
Section: Discussionmentioning
confidence: 99%